Editorial (GnosisWisdom, 2024)
The Journal of Scientific and Technological Research and Innovation GnosisWisdom, presents Vol.4, No. 1 (2024) is a peer-reviewed publication managed through the Open Journal System. Its objective is global dissemination, in its electronic version, it publishes original works on SOCIAL SCIENCE topics that retain a character of originality, usefulness, scientific and technological relevance; that provide new knowledge on theoretical or practical aspects in different areas of knowledge.